VEGF-Loaded Heparinised Gelatine-Hydroxyapatite-Tricalcium Phosphate Scaffold Accelerates Bone Regeneration via Enhancing Osteogenesis-Angiogenesis Coupling - Chen, Xu; Gao, Chun-Yan; Chu, Xiao-Yang; Zheng, Chun-Yan; Luan, Ying-Yi; He, Xin; Yang, Kai; Zhang, Dong-Liang (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Bone tissue defect, one of the common orthopaedic diseases, is traumatizing and affects patient’s lifestyle. Although autologous and xenograft bone transplantations are performed in bone tissue engineering, clinical development of bone transplantation is limited because of various factors, such as varying degrees of immune rejection, lack of bone sources, and secondary damage to bone harvesting. Methods: We synthesised a heparinised gelatine-hydroxyapatite-tricalcium phosphate (HG-HA-TCP) scaffold loaded with sustained-release vascular endothelial growth factor (VEGF) analysed their structure, mechanical properties, and biocompatibility. Additionally, the effects of HG-HA-TCP (VEGF) scaffolds on osteogenic differentiation and vascularisation of stem cells from human exfoliated deciduous teeth (SHED) in vitro and bone regeneration in vivo were investigated. Results: HG-HA-TCP scaffold possessed good pore structure, mechanical properties, and biocompatibility. HG-HA-TCP scaffold loaded with VEGF could effectively promote SHED proliferation, migration, and adhesion. Moreover, HG-HA-TCP (VEGF) scaffold increased the expression of osteogenesis- and angiogenesis-related genes and promoted osteogenic differentiation and vascularisation in cells. In vivo results demonstrated that VEGF-loaded HG-HA-TCP scaffold improved new bone regeneration and enhanced bone mineral density, revealed by histological, micro-CT and histochemical straining analyses. Osteogenic and angiogenic abilities of the three biological scaffolds were ranked as follows: HG-HA-TCP (VEGF) > G-HA-TCP (VEGF) > G-HA-TCP. Conclusion: HG-HA-TCP (VEGF) scaffold with good biocompatibility could create an encouraging osteogenic microenvironment that could accelerate vessel formation and osteogenesis, providing an effective scaffold for bone tissue engineering and developing new clinical treatment strategies for bone tissue defects.